(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the context of Ukraine’s strategic course toward European integration, ensuring transparency, accountability, and effective regulation in the financial sector has become increasingly vital. Banking and non-banking institutions face growing challenges related to fraud prevention, anti-money laundering, and compliance with international standards. As Ukraine adapts its legislation and practices to align with the EU acquis, financial compliance is gaining importance as a mechanism to strengthen institutional integrity and minimize risks. Aim. The primary objective of this study is to explore the role of financial compliance as an effective tool for minimizing legal, financial, and reputational risks in Ukraine’s financial sector, with a specific emphasis on aligning national practices with European Union standards and directives. Methods. The research employs theoretical, analytical, and comparative legal methods. Ukrainian legal acts are analyzed alongside key EU regulatory frameworks, including the Fifth Anti-Money Laundering Directive (AMLD5). Case studies from selected EU member states are used to identify best practices and assess their applicability in Ukraine. Results. The analysis reveals that while Ukraine has made significant progress in updating its compliance framework, systemic challenges persist. These include regulatory ambiguity, weak institutional capacity, a shortage of qualified compliance officers, and underdeveloped compliance cultures in financial institutions. In contrast, EU countries demonstrate the effectiveness of operationally independent compliance departments, clear legal mandates, and regular professional training. Conclusions. To enhance financial sector resilience and successfully implement EU compliance standards, Ukraine must adopt a comprehensive strategy that includes legal harmonization, developing a compliance infrastructure, and promoting ethical business practices. A robust compliance culture, supported by well-trained professionals and strong institutional frameworks, is essential for sustainable integration into the EU’s financial and legal space.